2021
DOI: 10.3389/fonc.2021.759840
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Radiomics Nomogram for Differentiating Pulmonary Cryptococcosis and Lung Adenocarcinoma in Solitary Pulmonary Solid Nodule

Abstract: ObjectiveTo establish a CT-based radiomics nomogram model for classifying pulmonary cryptococcosis (PC) and lung adenocarcinoma (LAC) in patients with a solitary pulmonary solid nodule (SPSN) and assess its differentiation ability.Materials and MethodsA total of 213 patients with PC and 213 cases of LAC (matched based on age and gender) were recruited into this retrospective research with their clinical characteristics and radiological features. High-dimensional radiomics features were acquired from each mask … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…After removing poorly reproducible and redundant features, the features were sorted using mRMR, and the top 100 features were ultimately selected for lasso screening. Four features were retained for both intra- and peri- nodular ( 17 ), and Intra-RS and Peri-RS models were established ( Figure 3 ). The G-RS model was built for the combined intra- and nodular features using forward stepwise multiple logical regression.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removing poorly reproducible and redundant features, the features were sorted using mRMR, and the top 100 features were ultimately selected for lasso screening. Four features were retained for both intra- and peri- nodular ( 17 ), and Intra-RS and Peri-RS models were established ( Figure 3 ). The G-RS model was built for the combined intra- and nodular features using forward stepwise multiple logical regression.…”
Section: Resultsmentioning
confidence: 99%
“…( 15 ) constructed an radiomics model to identify adenocarcinoma and granulomatous nodules in the lung with good performance, while Liu et al. ( 16 ) included different categories of benign nodules and showed that the diagnostic performance of the radiomics model was better than that of the Lung-RADS model, and the diagnostic performance of LDCT-based radiomic models to differentiate adenocarcinomas from benign lesions in solid pulmonary nodules were equivalent to that of standard-dose CT ( 17 ). constructed a clinical-radiomics model to identify pulmonary cryptococcosis and pulmonary adenocarcinoma, screening four visual radiological features of maximum diameter, size, lobulation and pleural retraction, consistent with our routine CT evaluation, including 24 radiomics features of different categories, with wavelet features as the main part (19/24), quantifying the heterogeneity of lesions of different grades that are not recognized by human eyes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations